Water-filtered Infrared A (wIRA) Irradiation From Research to Clinical Settings - Vaupel, Peter (Springer International Publishing : Imprint: Springer, 2022)
The aim of this open access book is to provide a unique, timely, critical and comprehensive compilation of more than 30 years of robust international experimental and clinical research related to the basic science and therapeutic application of water-filtered infrared-A (wIRA) and hyperthermia in oncology, psychiatry (depression), musculoskeletal disorders, dermatology, infectiology, and surgery. This is an internationally absolutely unique attempt which publication is timely and of great interest in medical as well as in natural sciences. The aim is to enhance communication and advance the use of heat therapy for patient benefit, and to generate an environment in which anyone with an interest in hyperthermia can discuss, collaborate, network, and share events and resources. Productive dialogue and discussion among scientists and practitioners on issues relating to hyperthermia therapy is essential, especially relating to thermal transmission by water-filtered infrared-A (wIRA). The specificity and advantage of this technology is its tolerance by tissue, and its penetration of up to 3 cm allows the delivery of high heat dosages that are relevant across multiple clinical indications. Currently, wIRA is being applied in Austria, Germany, Portugal, Switzerland, The Netherlands, UK and the USA. The authors' hope is that its use will increase in these countries, and also expand into others. This book will be an invaluable tool for oncologists, surgeons, dermatologists as well as physiotherapists.